Symposium 3: (Dis)connective Practice in Heterotopic Spaces for Networked and Connected Learning - Bell, Frances (Proceedings of the International Conference on Networked Learning, 2016)
This paper explores the implications of learners’ and educators’ appropriation of Social Networking Sites (SNS) for informal open, networked and connected learning through the lens of learner practices within sociotechnical assemblages. Relevant themes identified from the literature are the impact of an advocacy approach in open, networked and connected learning; the mutuality of openness and closure; time-space online; connective and dis-connective practices and heterotopias. A theory of Disconnective Practice has been developed by Light in relation to SNS that helps us to understand practice through considering disconnection as well as the more usual perspective of connection. Mejias' critique of the nodocentric view presented by SNS can help by alerting us to the concept of paranodes, spaces that lie beyond the logic of the network. Providers of SNS benefit from connection, media production and sharing by members that enhance their advertising services. I explore heterotopias, unsettling fragmentary places, in open practice using two vignettes of PhD students, one in a social context and another in a research context. The first vignette explores the global nature of context and culture collapse across SNS, as a student moves to a different country and culture to undertake PhD study. This vignette highlights the impact of the combination of persistent data and (hyper)connection to extended and invisible audiences. The second vignette explores how different regimes of Open Access publishing operate within the politics of Higher Education (HE) contexts. Although heterotopias are important to open, networked and connected learning they can be difficult to achieve: disconnective practice can help. Networks crave connection and resist our scrutiny. Thus learners need to be able to practice disconnection as well as connection, and be able and prepared to challenge the logic of SNS and institutional systems. How can digital literacy practices of learners and teachers take account of learning on SNS when the focus of SNS is to benefit advertising services that are the actual customers?